Perfil de resistência a antibióticos e metais em bactérias isoladas dos rios Pajuçara e Curuai em Santarém, Pará - SILVA, Beatriz Lobato da (2024)
The present work seeks to identify and characterize the antibiotic and metal resistance profile of Gram-negative bacteria isolated from the Pajuçara and Curuai rivers, relating it to the environmental impact caused by human activities in the vicinity of these environments. For this, the strains isolated from the rivers had their DNA extracted and amplified for sequencing the 16s rRNA gene, and were subjected to sensitivity tests to 16 antibiotics (beta-lactams, aminoglycosides, tetracyclines, sulfonamides, quinolones and chloramphenicols) and 2 heavy metals (Arsenic and Manganese), through disk diffusion and plate microdilution methods for minimum inhibitory concentration. The most predominant genus among the isolates was Klebsiella (approximately 45.5%), followed by Stenotrophomonas (36.4%), Achromobacter and Shigella (both 9.1%). About 27.27% of the isolates showed multidrug resistance, that is, resistance to at least 3 classes of antibiotics. All isolates were resistant to amoxicillin, ampicillin and cephalothin, and sensitive to ciprofloxacin and sulfazotrim. Isolates from the genera Stenotrophomonas and Achromobacter exhibited the highest rates of antimicrobial resistance, and also obtained the highest values of minimum inhibitory concentration to the two metals tested.